Long-Term Recidivism of Mentally Disordered Offenders Considered “Dangerous to the Public” in Switzerland - Schaffner, Daniela; Weber, Michael; Kochuparackal, Tanya; Graf, Marc; Hachtel, Henning (Frontiers in Psychiatry, 2021)
Objectives: The commissions for risk assessment of offenders dangerous to the public were established in 1995 in Switzerland. The main goal was to reduce recidivism of offenders released into the community by means of identifying high-risk offenders and recommending measures for offender management. This study investigates long-term recidivism data of this high-risk cohort of offenders. Methods: Baseline data included risk assessment of one of the commissions, the type of index offense, and psychiatric disorders according to ICD-10 for the total cohort of offenders examined by the commissions between 1995 and 2009. Criminal records were drawn in 2019 for all offenders from the Swiss Federal Office of Justice. Results: From a total of 147 offenders 35 recidivated within a median time at risk of 9.1 years (31.8%), of which 10 (9.1 %) recommitted a severe offense. Within the treatment status, sentences (imprisonment and preventive detention) were compared to court-ordered measures (in- or outpatient court ordered treatment, civil court mandated treatment, vocational training facility). There were no significant differences comparing treatment status, different diagnostic groups, type of index offense and other risk factors. Except of age at release (or relapse), which predicted recidivism with younger subjects showing higher recidivism rates (p=.014). Conclusion: Our study showed that over a long-term time at risk this high-risk cohort showed a similar recidivism rate as many other studies with different cohorts. With appropriate management recidivism rates in high-risk offenders can be lowered allowing them being consecutively reintegrated into society. The finding that younger subjects have higher recidivism rate was reproduced in this population.